2013
DOI: 10.7314/apjcp.2013.14.11.7033
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Cancer in Kazakhstan - Ethnic, Age and Gender Differences over Time

Abstract: The purpose of the present study was to provide an assessment of the incidence of cancer of the larynx in Kazakhstan with especial attention to ethnicity and gender, as well as age. In the dynamics, the rates had the tendency to decrease more markedly in Russian than Kazakh men, especially in the younger groups, while increase was noted in the youngest females of both ethnicities, but again greater in Russians, presumably reflecting change in underlying lifestyle factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…The incidence rates of laryngeal carcinoma are considerably lower among the female patients [6][7][8][9]. We report 34 female patients-who met the inclusion criteria-with laryngeal carcinoma; 38.2% were in the fifth decade of life, and these results are in accordance with the report of Garham and Palmer [10].…”
Section: Discussionsupporting
confidence: 88%
“…The incidence rates of laryngeal carcinoma are considerably lower among the female patients [6][7][8][9]. We report 34 female patients-who met the inclusion criteria-with laryngeal carcinoma; 38.2% were in the fifth decade of life, and these results are in accordance with the report of Garham and Palmer [10].…”
Section: Discussionsupporting
confidence: 88%
“…Epidemiological research pursued in Kazakhstan has shown that the pattern of laryngeal cancer, leukemia and breast cancer prevalence depends on ethnic and gender differences, unfavorable environmental conditions (Bilyalova et al, 2012;Igissinov et al, 2012;Igissinov et al, 2013) . Previous research has shown that technogenic chrome biogeochemical province has a direct impact on the prevalence of malignant tumors among the urban residents and cancer pathologymortality rate .…”
Section: Introductionmentioning
confidence: 99%